1998
DOI: 10.1128/aem.64.9.3359-3367.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Defined 2,3,5,6-Tetrachlorobiphenyl- ortho -Dechlorinating Microbial Community by Comparative Sequence Analysis of Genes Coding for 16S rRNA

Abstract: Defined microbial communities were developed by combining selective enrichment with molecular monitoring of total community genes coding for 16S rRNAs (16S rDNAs) to identify potential polychlorinated biphenyl (PCB)-dechlorinating anaerobes that orthodechlorinate 2,3,5,6-tetrachlorobiphenyl. In enrichment cultures that contained a defined estuarine medium, three fatty acids, and sterile sediment, a Clostridium sp. was predominant in the absence of added PCB, but undescribed species in the δ subgroup of the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 36 publications
4
30
0
Order By: Relevance
“…Therefore, it was possible that the dechlorinating microorganisms and the methanogens might compete for the acetate or the methanogens might dechlorinate the PCB. Previously it was demonstrated that sediment‐containing precursors to the ortho ‐dechlorinating culture would dechlorinate 2,3,5,6‐CB in the absence of methanogenesis when 3 mM bromoethanesulphonate (BES) and 5 mM sodium acetate were added (Pulliam Holoman et al ., 1998). Here, in contrast, amendment of the sediment‐free ortho ‐dechlorinating culture with 1–3 mM BES and 5 mM acetate resulted in a reduction of dechlorinating activity below detectable levels.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was possible that the dechlorinating microorganisms and the methanogens might compete for the acetate or the methanogens might dechlorinate the PCB. Previously it was demonstrated that sediment‐containing precursors to the ortho ‐dechlorinating culture would dechlorinate 2,3,5,6‐CB in the absence of methanogenesis when 3 mM bromoethanesulphonate (BES) and 5 mM sodium acetate were added (Pulliam Holoman et al ., 1998). Here, in contrast, amendment of the sediment‐free ortho ‐dechlorinating culture with 1–3 mM BES and 5 mM acetate resulted in a reduction of dechlorinating activity below detectable levels.…”
Section: Resultsmentioning
confidence: 99%
“…For example, anaerobic dechlorinators of polychlorinated biphenyls (PCBs) are present at a low density in the environment, which did not allow detection by classical methods. Their identification required successive enrichments combined with the monitoring of dechlorination activity and 16S rRNA gene patterns (Pulliam Holoman et al , 1998). This might also be relevant for microorganisms producing natural products such as enzymes or antibiotics.…”
Section: Soil Metagenome Exploitationmentioning
confidence: 99%
“…The sample and buffers were mixed by hand prior to 30 s of bead beating at speed '4.5' using a FastPrep120 (Q-Biogene, CA). Nucleic acid extraction and purification were performed using a phenol/chloroform-based protocol (Pulliam Holoman et al, 1998).…”
Section: Dna Extraction From Sediments and Microcosmsmentioning
confidence: 99%